Anthropogenic non-methane volatile hydrocarbons at Mt. Cimone (2165 m a.s.l., Italy): Impact of sources and transport on atmospheric composition. (September 2016) - Lo Vullo, Eleonora; Furlani, Francesco; Arduini, Jgor; Giostra, Umberto; Graziosi, Francesco; Cristofanelli, Paolo; Williams, Martin L.; Maione, Michela
Abstract: To advance our understanding of the factors that affect pollution in mountainous areas, long-term, high frequency measurements of thirteen Non Methane Volatile Organic Compounds (NMVOCs) have been carried out at the atmospheric observatory on the top of Mt. Cimone (2165 m a.s.l.), whose location is ideal for sampling both aged air masses representing the regional background and polluted air masses coming from nearby sources of anthropogenic pollution. An analysis of the NMVOC time series available at Mt. Cimone during 2010–2014 was used to examine the influence of transport processes on NMVOC atmospheric composition and to derive information on the emission sources. We performed a multifactor principal component analysis whose results allowed us to identify the source categories emitting the NMVOCs measured at Mt. Cimone as well as to assess transport ranges in winter and summer. Aged air masses, due to long-range transport and related to vehicular traffic exhaust emissions accounted for 78% of the NMVOC variability in winter and 62% in summer, whereas evaporative emissions, likely to be associated with fresh emissions from nearby sources, accounted for 12% of the NMVOC variability and 24% in winter and summer, respectively. Such results have been confirmed by a further analysis in which the NMVOC variability as a function of their atmospheric lifetimes has been evaluated. The ratios of alkane isomers potentially provides a metric to investigate seasonal changes in NMVOCs composition and in the emission fields of butanes and pentanes, suggesting that during the summer the butanes are originating mainly from the European domain and that for pentanes non-anthropogenic sources may be contributing to the measured concentrations. Highlights: NMVOC speciation profile is site-specific and so is its impact on air quality and climate. Vehicular traffic exhaust emissions are the prevailing source category in our study area. Different seasonal patterns are observed corresponding to different transport ranges.